Wiskott-Aldrich syndrome protein interacts and inhibits diacylglycerol kinase alpha promoting IL-2 induction - Velnati, Suresh; Centonze, Sara; Rossino, Giulia; Purghè, Beatrice; Antona, Annamaria; Racca, Luisa; Mula, Sabrina; Ruffo, Elisa; Malacarne, Valeria; Malerba, Mario; Manfredi, Marcello; Graziani, Andrea; et al. (Frontiers in Immunology, 2023)
Background Phosphorylation of diacylglycerol by diacylglycerol-kinases represents a major inhibitory event constraining T cell activation upon antigen engagement. Efficient TCR signalling requires the inhibition of the alpha isoform of diacylglycerol kinase, DGKα, by an unidentified signalling pathway triggered by the protein adaptor SAP. We previously demonstrated that, in SAP absence, excessive DGKα activity makes the T cells resistant to restimulation-induced cell death (RICD), an apoptotic program counteracting excessive T cell clonal expansion. Results Herein, we report that the Wiskott-Aldrich syndrome protein (WASp) inhibits DGKα through a specific interaction of the DGKα recoverin homology domain with the WH1 domain of WASp. Indeed, WASp is necessary and sufficient for DGKα inhibition, and this WASp function is independent of ARP2/3 activity. The adaptor protein NCK-1 and the small G protein CDC42 connect WASp-mediated DGKα inhibition to SAP and the TCR signalosome. In primary human T cells, this new signalling pathway is necessary for a full response in terms of IL-2 production, while minimally affecting TCR signalling and restimulation-induced cell death. Conversely, in T cells made resistant to RICD by SAP silencing, the enhanced DAG signalling due to DGKα inhibition is sufficient to restore apoptosis sensitivity. Conclusion We discover a novel signalling pathway where, upon strong TCR activation, the complex between WASp and DGKα blocks DGKα activity, allowing a full cytokine response.